2013
DOI: 10.1093/hmg/ddt427
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs derived from lncRNA RNase MRP have gene-silencing activity relevant to human cartilage–hair hypoplasia

Abstract: Post-transcriptional processing of some long non-coding RNAs (lncRNAs) reveals that they are a source of miRNAs. We show that the 268-nt non-coding RNA component of mitochondrial RNA processing endoribonuclease, (RNase MRP), is the source of at least two short (∼20 nt) RNAs designated RMRP-S1 and RMRP-S2, which function as miRNAs. Point mutations in RNase MRP cause human cartilage-hair hypoplasia (CHH), and several disease-causing mutations map to RMRP-S1 and -S2. SHAPE chemical probing identified two alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 74 publications
1
76
0
Order By: Relevance
“…27). Recently, Rogler and colleagues reported that RNase MRP (a 268 bp noncoding RNA component of mitochondrial RNA processing endoribonuclease) was the source for two short (around 20 bp) RNAs important in the biology of cartilage-hair hypoplasia (13). As such, we hypothesized that one role for PCA3 could be as a source for short biologically active species.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…27). Recently, Rogler and colleagues reported that RNase MRP (a 268 bp noncoding RNA component of mitochondrial RNA processing endoribonuclease) was the source for two short (around 20 bp) RNAs important in the biology of cartilage-hair hypoplasia (13). As such, we hypothesized that one role for PCA3 could be as a source for short biologically active species.…”
Section: Discussionmentioning
confidence: 94%
“…The GENCODE consortium recently annotated 9,277 lncRNA genes, corresponding to 14,880 transcripts (11). In contrast with protein coding genes, lncRNAs typically have few gene exons, can be processed into active short species (12)(13)(14), and are not conserved from primitive species (15). As no functional role for PCA3 has been assigned to date, we wondered whether this ncRNA might encode an active shorter species.…”
Section: Introductionmentioning
confidence: 99%
“…S1F). While it is intriguing that an siRNA targeting the ncRNA subunit of RNase MRP would also target the messages for its protein subunits and that microRNAs (miRNAs) derived from the MRP RNA locus closely overlap the siRNA sequence examined here (Rogler et al 2014), this reagent's effect was too pleiotropic to examine MRP RNA-specific function and was not pursued further.…”
Section: Resultsmentioning
confidence: 99%
“…human disease phenotypes (Halvorsen et al 2010;Martin et al 2012;Jafarifar et al 2014;Rogler et al 2014;Kutchko et al 2015). However, it is likely that the vast majority of natural and somatic genetic variation is phenotypically benign.…”
Section: Lackey 16mentioning
confidence: 99%